Analisis Good Corporate Governance dan Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan - Riyana Farida; Ahmad Hijri Alfian (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to determine the influence of the board of directors, audit committee, independent commissioners, managerial ownership, and Corporate Social Responsibility on the financial performance of companies listed on the IDX-MES BUMN 17 for the 2021-2023 period. The population in this study is all companies listed on the IDX-MES BUMN 17 during the 2021-2023 period. This study uses a sampling technique, namely the purposive sampling method by taking samples from the population, selected companies that meet the criteria to be sampled as many as 16 companies, the data used in this study is secondary data obtained from the annual reports and sustainability reports of each company. The results of this study indicate that the board of directors has a significant negative effect on financial performance based on a coefficient value of -0.007 with a significance value of 0.034. The audit committee, independent commissioners and Corporate Social Responsibility (CSR) have a positive and significant effect on the company's financial performance based on a significance value <0.05. Meanwhile, managerial ownership does not affect financial performance based on a regression coefficient of 1.825 with a significance value of 0.587.